ANALISIS CROWDING OUT EFFECT PENERBITAN OBLIGASINEGARA: STUDIKASUS PEREKONOMIAN INDONESIA PERIODE 1970 - 2003 - Waluyo, Joko (Universitas Muhammdaiyah Surakarta, 2006)
The main subject of this research are to proof what issuing government bonds give impact to crowding out effect for private investment. The research design used simultaneous equation modeling, consisting of 17 behavioral equation and 18 identity equation with 6 blocks. Behavioral equation with estimated by tsls (two stage least square). This study use secondary data from Indonesian economy since 1970 until 2003. The econometric test to result BLUE estimator. The Result is issuing government bonds dont cause crowding out effect to private investment.